2018
DOI: 10.1016/j.ajodo.2017.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional treatment outcomes in Class II patients with different vertical facial patterns treated with the Herbst appliance

Abstract: Approximately 2 years after Herbst treatment, the Herbst subjects with different vertical facial patterns showed similar patterns of skeletal change compared with the Class II controls treated with elastics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 44 publications
2
43
1
Order By: Relevance
“…If a smaller clinical tolerance were considered, a smaller effect size would recommend a significantly greater amount of patients, which due to the retrospective design of the current investigation would not be feasible. Therefore, the current findings need to be interpreted with caution, despite that our findings are very similar to previously reported data, suggesting the generalizability (external validity) of the study results. A prospective randomized clinical trial would compensate for such weaknesses, and however, due to the current ALARA principle it would not be ethical to run prospective studies with CBCT in children.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…If a smaller clinical tolerance were considered, a smaller effect size would recommend a significantly greater amount of patients, which due to the retrospective design of the current investigation would not be feasible. Therefore, the current findings need to be interpreted with caution, despite that our findings are very similar to previously reported data, suggesting the generalizability (external validity) of the study results. A prospective randomized clinical trial would compensate for such weaknesses, and however, due to the current ALARA principle it would not be ethical to run prospective studies with CBCT in children.…”
Section: Discussionsupporting
confidence: 82%
“…They found that ‘ improved dental occlusion was not achieved at the price of a change to an unphysiological position in the temporomandibular joints’ . Recently, Atresh et al reported in adolescents 12 to 13 years of age at the beginning of treatment that there were no significant differences in the 3D positions of the geometric centre of the condyle after orthodontic treatment had been completed, with the overall trend resulting a slightly posterior displacement of both glenoid fossae and condyles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e effects on the dental component include a distalisation of the upper dental arch and a mesialisation of the lower dental arch [8], while the effects on the skeletal component include a decreased growth of the maxilla [9] and a stimulation of the mandibular growth with an increase in the average length at the end of treatment greater than 2-3 mm [10]. e mechanism permits vertical opening movements and effect on the vertical tooth position [11], and the skeletal effect is most pronounced during puberty rather than before [12]. e main disadvantage of the Herbst consists in a proclination of lower incisors due to anchorage loss in different amounts relative to the type of Herbst used [13]; various modifications of the original orthodontic appliance have been proposed, but none has been able to completely prevent proclination of mandibular incisors [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The Dental and Craniofacial Bionetwork for Image Analysis (DCBIA‐https://sites.google.com/a/umich.edu/dentistry-image-computing/) group is composed by researchers, clinicians, computer scientists and engineers with the aims to (a) develop image analysis tools specifically to answer dentistry‐related clinical questions; (b) train researchers interested in those tools. These efforts resulted in international collaborations with South America, Europe, Asia and Oceania, not to mention other centres within the United States, with a large variety of application of the tools as follows: craniofacial anomalies, asymmetry, surgical outcomes and growth changes . Strengthening the relationship with other centres may eventually facilitate the development of big data that require secure but easily accessible de‐identified databases, with storage, mining and analytics capabilities.…”
Section: Applications Of Open‐source Software To Collaborative Clinicmentioning
confidence: 99%